Hakim Konstitusi di Persimpangan Jalan: Kuasa Lembaga Pengusul dalam Pemberhentian yang Kontroversial - Isthifailla, Isthifailla; Pratama, Agung Barok (Manabia: Journal of Constitutional Law, 2024)
The process for selecting Constitutional Court judges involves three branches of government: the House of Representatives (legislative), the President (executive), and the Supreme Court (judicial). This arrangement is intended to ensure integrity, independence, and proper oversight. Normatively, neither the House of Representatives, the President, nor the Supreme Court has the authority to dismiss a Constitutional Court judge they have proposed. However, on September 29, 2022, the House of Representatives removed Judge Aswanto from the Constitutional Court, citing his frequent annulment of legislation enacted by the House of Representatives as the reason. This study aims to analyze the dismissal of Constitutional Court judges by the proposing institution. It employs a normative legal research method, utilizing legislative, case, and conceptual approaches. The findings indicate that Judge Aswanto's dismissal was inconsistent with Article 23, paragraph (4) of the Constitutional Court Law, which stipulates that "The dismissal of a Constitutional Judge may be made based on a Presidential Decree upon the request of the Chairperson of the Constitutional Court." This article clearly shows that the dismissal of Judge Aswanto by the proposing institution, namely the House of Representatives, constitutes a violation of the law and breaches the rule of law principle. Moreover, Judge Aswanto's dismissal has legal consequences, including representing an intervention by the proposing institution the House of Representatives  into the Constitutional Court, which undermines the independence and impartiality of the Court.